بعض القدرات الحركیة وعلاقتھا بمستوى الاداء المھاري لدى لاعبي التایكواندو الشباب - علي سلمان الطرفي; واثق عايد كاظم (الرياضة المعاصرة, 2016)
1-A research on the simple introduction to the game of Taekwondo and the research problem and capacity of contribution to performance skills in taekwondo. As well as the imposition of research( there is relationship objectives of the research .which (indenfiy to motor between the level of some motor skill and capacities in Taekwondo.) relation also included a sample research 25 players. 2-Ensure that the door presentation of the results of statistical processing using a set of tables, and then analysed and discussed in a scientific sources through this discussion and then to reach the goals of the research and verification of the hypothesis . 3. Conclusion included the conclusions of which( there is a correlation of meaning between flexibility and balance with the skill of hacking side and recommendation of which exercise performance through combined with kinetic elements of flexibility and balance